2014
DOI: 10.1371/journal.pone.0116002
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Expression of Ethylene-Related Genes and Papaya Fruit Ripening Disorder Caused by Chilling Injury

Abstract: Papaya (Carica papaya L.) is sensitive to low temperature and easy to be subjected to chilling injury, which causes fruit ripening disorder. This study aimed to investigate the relationship between the expression of genes related to ethylene and fruit ripening disorder caused by chilling injury. Papaya fruits were firstly stored at 7°C and 12°C for 25 and 30 days, respectively, then treated with exogenous ethylene and followed by ripening at 25°C for 5 days. Chilling injury symptoms such as pulp water soaking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 59 publications
1
34
0
1
Order By: Relevance
“…Whereas, papaya fruit is considered to be susceptible to cold storage . Temperatures below 7 °C induce CI in papaya fruits and cause fruit ripening disorder . As shown in Fig.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Whereas, papaya fruit is considered to be susceptible to cold storage . Temperatures below 7 °C induce CI in papaya fruits and cause fruit ripening disorder . As shown in Fig.…”
Section: Resultssupporting
confidence: 77%
“…Papaya ( Carica papaya L.) fruit is one of the most important tropical fruits in the world. As a typical climacteric fruit, papaya fruit has rapid softening and yellowing processes, which results in short‐term shelf life during postharvest storage . Therefore, despite its high nutritional value and demand on the market, papaya fruit is rather difficult to preserve and commercialize .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ripening process of climacteric fruit is accompanied by a peak in ethylene production and thus results in a dramatic decrease in fruit hardness (Costa et al , ). ERFs, signal factors that bridge the internal and external signal and ethylene response, play important roles in stress responses (Liu et al , , , ; Zou et al , ), growth and development (Yin et al , ) and senescence (Tomotsugu et al , ). It has been reported that ERFs could be candidate genes for fruit firmness.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in the cold-sensitive Fortune mandarin, the continuous ET application during cold storage induces cold tolerance through the increase of CAT and PAL activities . However, the induction of ACS and ACO gene expression during lowtemperature storage does not represent an accurate indicator of cold tolerance since it has been described in cold-sensitive citrus fruit (Maul et al 2011 ;Lado et al 2014Lado et al , 2015, papaya (Zou et al 2014 ), and zucchini (Megías et al 2014 ), whereas it was not observed in grapefruit cold-resistant tissues (Lado et al 2015 ). However, the induction of ACS and ACO gene expression during lowtemperature storage does not represent an accurate indicator of cold tolerance since it has been described in cold-sensitive citrus fruit (Maul et al 2011 ;Lado et al 2014Lado et al , 2015, papaya (Zou et al 2014 ), and zucchini (Megías et al 2014 ), whereas it was not observed in grapefruit cold-resistant tissues (Lado et al 2015 ).…”
Section: Phytohormones and Cold Tolerance During Fruit Ripening And Pmentioning
confidence: 99%